2022
DOI: 10.1093/hr/uhac005
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-level genome assembly of Aristolochia contorta provides insights into the biosynthesis of benzylisoquinoline alkaloids and aristolochic acids

Abstract: Aristolochic acids (AAs) and their derivatives exist in multiple Aristolochiaceae species which had been or are being used as medicinal materials. During the past decades, AAs have received increasing attention due to their nephrotoxicity and carcinogenecity. Elimination of AAs in medicinal materials using biotechnological approaches is important to improve medication safety. However, it has not been achieved because of the limited information of AA biosynthesis available. Here, we report a high-quality refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 116 publications
(140 reference statements)
4
29
0
Order By: Relevance
“…Because previous studies have described WGD events in L. chinense (Ks ~ 0.7) and C. kanehirae (Ks ~ 0.5 and Ks ~ 0.8), both species were used as control of the results obtained. Ks distribution analysis suggested the absence of a WGD event in A. cherimola , confirming the results in other species belonging to the Magnoliid clade, such as A. fimbriata (Qin et al, 2021) and A. contorta (Cui et al, 2022). However, work on the M. biondii genome (Dong et al, 2021) suggested that a WGD event took place just before the separation between Magnoliales and Laurales, in agreement with the genome evolution of Litsea (Chen, Li, et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Because previous studies have described WGD events in L. chinense (Ks ~ 0.7) and C. kanehirae (Ks ~ 0.5 and Ks ~ 0.8), both species were used as control of the results obtained. Ks distribution analysis suggested the absence of a WGD event in A. cherimola , confirming the results in other species belonging to the Magnoliid clade, such as A. fimbriata (Qin et al, 2021) and A. contorta (Cui et al, 2022). However, work on the M. biondii genome (Dong et al, 2021) suggested that a WGD event took place just before the separation between Magnoliales and Laurales, in agreement with the genome evolution of Litsea (Chen, Li, et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, although early divergent angiosperm phylogeny studies have been published, the relations among eudicots, monocots, and magnoliids are still incongruent, probably because of the limited informative sequence generated among these groups. To date, draft reference genomes have been published for 15 species of the Magnoliid clade: two in the Calycanthaceae (Laurales) ( Chimonanthus salicifolius [Lv et al, 2020] and Chimonanthus praecox [Shang et al, 2020; Shen et al, 2021]); seven in the Lauraceae (Laurales) ( Cinnamomum camphora [Shen et al, 2022; Jiang et al, 2022], Cinnamomum kanehirae [Chaw et al, 2019], Lindera glauca [Xiong et al, 2022], Litsea coreana [Zhang et al, 2022], Litsea cubeba [Chen, Hu, et al, 2020], Phoebe bournei [Han et al, 2022], and Persea americana [Nath et al, 2022; Rendón‐Anaya et al, 2019; Sharma et al, 2021; Talavera et al, 2019]); one in the Annonaceae (Magnoliales) ( A. muricata [Strijk et al, 2021]); three in the Magnoliaceae (Magnoliales) ( Liriodendron chinense [Chen, Hao, et al, 2019], Magnolia biondii [Dong et al, 2021], and Magnolia officinalis [Yin et al, 2021]); two in the Aristolochiaceae (Piperales) ( Aristolochia fimbriata [Qin et al, 2021] and Aristolochia contorta [Cui et al, 2022]); and one in the Piperaceae (Piperales) ( Piper nigrum [Hu et al, 2019]). Thus, Annonaceae, the largest family on this clade and one of the most species‐rich pantropical plant families (Couvreur et al, 2019), is only represented by one genome until now.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, the results of nuclear genome sequencing analysis of C. camphora , A. glabra, P. bournei, A. contorta , C. burmannii , etc. support that magnoliids are sister plants to eudicots ( Cui et al., 2022 ; Han et al., 2022 ; He et al., 2022 ; Li et al., 2022 ; Shen et al., 2022 ; Sun et al., 2022 ; Wang et al., 2022 ).…”
Section: Phylogeny Based On the Sequencing Of Magnoliids Own Nuclear ...mentioning
confidence: 95%
“…The reported species of magnoliids with sequenced nuclear genomes include Magnoliales, Laurales, and Piperales (17 species, 23 references in total). Examples include Laurales: Cinnamomum kanehirae ( Chaw et al., 2019 ), avocado ( Persea americana ) ( Rendón-Anaya et al., 2019 ; Nath et al., 2022 ), Litsea cubeba ( Chen Y. C. et al., 2020 ), Phoebe bournei ( Chen S. P. et al., 2020 ; Han et al., 2022 ), Cinnamomum camphora ( Jiang et al., 2022 ; Shen et al., 2022 ; Sun et al., 2022 ; Wang et al., 2022 ), C. burmannii ( Li et al., 2022 ), Litsea coreana ( Zhang et al., 2022 ) of Lauraceae, Chimonanthus praecox ( Shang et al., 2020 ; Shen et al., 2021 ) and C. salicifolius ( Lv et al., 2020 ) of Calycanthaceae; Magnoliales: L. chinense ( Chen et al., 2019 ), Magnolia biondii ( Dong et al., 2021 ), M. officinalis ( Yin et al., 2021 ); Annona muricata ( Strijk et al., 2021 ), A. glabra ( He et al., 2022 ); Pepperales: Piper nigrum ( Hu et al., 2019 ), Aristolochia fimbriata ( Qin et al., 2021 ) and A. contorta ( Cui et al., 2022 ). Twenty of the 23 references in the genome analysis magnoliids discussed the evolutionary status of magnoliids, providing new insights into the early evolution of angiosperms, but the results of the analysis are inconsistent.…”
Section: Phylogeny Based On the Sequencing Of Magnoliids Own Nuclear ...mentioning
confidence: 99%
“…The protein sequences of the reference gene families involved in flavonoid and triterpenoid biosynthesis in A. thaliana or P. ginseng were downloaded from UniProt. These sequences were used as a query for a BLAST search against the protein sequences of AMM with an e value cutoff of 1e −40 ( Cui et al., 2022 ). Next, all the homologous sequences were submitted to the Pfam database for domain analysis ( Mistry et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%